Enhancing Problem-Solving Skills and Learning Motivation Through Problem-Based Learning Modules in Biology Education - Fadwa, Frida; Muhibbuddin, Muhibbuddin; Rahmatan, Hafnati; Artika, Wiwit; Sarong, Muhammad Ali (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
Problem-solving skills and learning motivation are essential components of 21st-century education, particularly in biology, where these competencies enable students to connect scientific concepts to real-world challenges. This study investigates the effectiveness of problem-based learning modules integrated with student worksheets in enhancing problem-solving skills and learning motivation on the topic of global warming. Conducted with tenth-grade students at a private high school in Banda Aceh, Indonesia, the research utilized an experimental design with pretest-posttest control groups. A total of 72 students were divided into experimental and control groups. Data collection included problem-solving skills tests based on Polya's framework and learning motivation questionnaires developed using Keller's ARCS model. The results revealed significant improvements in the experimental group, with an average normalized gain score of 77 for problem-solving skills, categorized as high, compared to 22 in the control group, categorized as low. Furthermore, the experimental group demonstrated strong learning motivation across all ARCS indicators. A correlation test indicated a very strong relationship between learning motivation and problem-solving skills, with motivation accounting for 74% of the variance in problem-solving performance. These findings underscore the effectiveness of problem-based learning modules in fostering critical competencies, supporting their integration into biology education to prepare students for future challenges. Further research is recommended to extend this approach to other scientific topics and diverse student populations.